Pengelolaan Sampah di Wilayah Jembatan dan Tepi Sungai Bungus Barat Menggunakan Pendekatan 3R: Reduce, Reuse, Dan Recycle - Rahim, Bulkia; Cintia Gusti Ansary; Mustika Sari, Dian; Yola Lestari, Dian; Sama Dortina Hutabarat, Ruth; Mardiana, Yuspita (J-CoSE: Journal of Community Service & Empowerment, 2024)
The increasing amount of waste presents an ongoing challenge in today's society. Inadequate mindsets, attitudes and behavior in waste management can create additional challenges that include social, environmental and health problems. From an environmental perspective, water systems can be adversely impacted, causing water pollution and flooding due to inappropriate waste disposal practices during periods of heavy rain. The decline in water quality around the bridge and both banks of the Sibungus River is getting worse. One factor that contributes to environmental degradation is the dumping of waste into rivers, a practice often carried out by individuals who live or carry out activities along riverbanks. Therefore, it is very important for individuals who live or carry out activities near rivers to prioritize reducing waste discharge into these water bodies. Current efforts to mitigate river pollution from waste are still limited, and this situation is further exacerbated by weak enforcement of environmental regulations against those responsible for pollution. Therefore, to maintain good water environmental conditions, mitigating river pollution due to waste requires extensive and comprehensive efforts. Government policies must actively encourage the implementation of the 3R approach in waste management, which includes the principles of reduction, transformation and disposal.